Unpacking the challenges of wildlife governance in community‐based conservation programs to promote human–wildlife coexistence. Issue 10 (19th August 2022) - Kansky, Ruth
Abstract: One of the numerous global challenges today is how to promote biodiversity persistence and at the same time reduce poverty and improve livelihoods, especially in multiple‐use landscapes shared by people and wildlife. In such landscapes, where the cost of sharing the landscape with large wildlife can be high, Community Based Natural Resource Management (CBNRM) program is a model promoted to offset negative wildlife impacts. However, such programs, that promote sustainable utilization of wildlife, are not always successful. To better understand how CBNRM governance systems enable or hinder human–wildlife coexistence, I implemented an 11‐weeks participatory co‐learning program in conservancies in the Zambezi region of Namibia. Framing human–wildlife relationships as occurring within complex social–ecological systems, participatory dialogues were used to unpack the system to better understand why human–wildlife conflict remains a challenge after 30 years of CBNRM in Namibia. From listening to communities I identified five key areas requiring improvement: (1) inefficient communication and transfer of information between management and community; (2) lack of policy and process clarity; (3) lack of support, knowledge, resources, and implementation of mitigation measures; (4) lack of accountability by both management and conservancy members; and (5) lack of skills and capacity by both management and conservancy members. To address these problem areas, I propose three key priority actions: (1) harmonize conservancy policies and management practices; (2) improve information flow; and (3) implement an adaptive management mitigation measure program. While this study focused on a small part of Namibia, I expect this methodology and many of the key findings and proposed interventions will be relevant for other areas applying collaborative approaches to improve human–wildlife coexistence.